Gamma-irradiation induced functionalization of graphene oxide with organosilanes - Aujara, Kabiru Musa; Chieng, Buong Woei; Ibrahim, Nor Azowa; Zainuddin, Norhazlin; Ratnam, Chantara Thevy (MDPI, 2019)
Gamma-ray radiation was used as a clean and easy method for turning the physicochemical properties of graphene oxide (GO) in this study. Silane functionalized-GO were synthesized by chemically grafting 3-aminopropyltriethoxysilane (APTES) and 3-glycidyloxypropyltrimethoxysilane (GPTES) onto GO surface using gamma-ray irradiation. This established non-contact process is used to create a reductive medium which is deemed simpler, purer and less harmful compared conventional chemical reduction. The resulting functionalized-GO were characterized by Fourier transform infrared spectroscopy (FT-IR), X-ray diffraction (XRD), field emission scanning electron microscopy (FE-SEM), thermogravimetric analysis (TGA), and Raman spectroscopy. The chemical interaction of silane with the GO surface was confirmed by FT-IR. X-ray diffraction reveals the change in the crystalline phases was due to surface functionalization. Surface defects of the GO due to the introduction of silane mioties was revealed by Raman spectroscopy. Thermogravimetric analysis of the functionalized-GO exhibits a multiple peaks in the temperature range of 200–650 °C which corresponds to the degradation of chemically grafted silane on the GO surface.